Development of acoustic target strength near-field equation for underwater vehicles. (August 2019) - Kim, Jae-Yong; Hong, Suk-Yoon; Cho, Byung-Gu; Song, Jee-Hun; Kwon, Hyun-Wung
For modern weapon systems, the most important factor in survivability is detection capability. Acoustic target strength is a major parameter of the active sonar equation. The traditional target strength equation used to predict the re-radiated intensity for the far field is derived with a plane-wave assumption. In this study, a near-field target strength equation was derived without a plane-wave assumption for a polygonal plate. The target strength equation for polygonal plates, which is applicable to the near field, is provided by the Helmholtz–Kirchhoff formula that is used as the primary equation for solving the re-radiated pressure field. A generalized definition of the sonar cross section is suggested that is applicable to the near field. In comparison experiments for a cylinder, the target strength equation for polygonal plates in near field was executed to verify the validity and accuracy of the analysis. In addition, an underwater vehicle model was analyzed with the developed near-field equation to confirm various parameter effects such as distance and frequency.